Value attribution for oncology combination regimens: going beyond frameworks to balance innovation, access, and affordability - Gaultney, Jennifer G.; Ollendorf, Daniel; Sasane, Medha; Fernandez, Céline; Paranjpe, Krupa; Chen, Ting-Yen; Sandhu, Hera; Simoens, Steven (Frontiers in Pharmacology, 2025)
Combination therapies are a mainstay in cancer treatment, but reimbursement access can be limited, owing to complexities around value assessment and pricing, and budget impact. Traditional frameworks for value assessment lack specific methodologies for evaluating combinations. A key challenge is value attribution between components. Here we provide the authors’ perspectives on this challenge, along with a summary of current market approaches and two proposed value attribution frameworks (VAFs), including their limitations and what would be needed to apply them in practice. Access to combination therapies varies by country, with each nation adopting different strategies to address challenges. Many have focused their efforts on competition laws, pricing, and overall affordability rather than value attribution. A value attribution solution could provide a basis for pricing and reimbursement negotiations for combinations. The two proposed VAFs offer a possible quantitative solution to assess the value of combination therapy components. However, existing VAFs are still limited by their data requirements and high levels of uncertainty, and are not applicable in certain market archetypes. Further work is needed before such VAFs can be widely applied. In addition, value attribution is only one component of the issue; locally tailored frameworks, agreement on criteria, multi-stakeholder collaboration, and a broader negotiation strategy encompassing other solutions are also necessary. We summarize key challenges and market approaches, as well as factors needed to make the proposed approaches acceptable.